Polyethylene composition for blow molding comprising waste recycled polyethylene

By using a composition containing waste recovery polyethylene and polyethylene with a three-peak molecular weight distribution, the shortcomings in the mechanical properties of waste recovery polyethylene are solved, and the high mechanical properties of the products in the blow molding process are achieved.

CN119768464APending Publication Date: 2025-04-04BASELL POLYOLEFINE GMBH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380061069.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-20
Filing Date
2023-09-18
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The waste recycling polyethylene has problems with poor impact strength, insufficient environmental stress cracking resistance and difficulty in processing into a final product with satisfactory properties, especially in blow molding processes.

Method used

A composition comprising 25% to 85% of waste recovery polyethylene and 15% to 75% of polyethylene with at least three peak molecular weight distribution is used, which has a range of optimization parameters in terms of density, melt flow index and melt index to improve mechanical properties.

Benefits of technology

With this polyethylene composition, the performance of waste recovery polyethylene in terms of impact strength, environmental stress crack resistance and welding strength can be significantly improved, thereby making the blow-molded product have better mechanical properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present disclosure relates to a polyethylene composition particularly suitable for blow molding, the polyethylene composition comprising: I) from 25% to 85% by weight of waste recycled polyethylene; iI) from 15% to 75% by weight of a polyethylene having an at least trimodal molecular weight distribution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to polyethylene compositions containing waste recycled polyethylene, which can be advantageously used to produce blow molded articles. Background Art

[0002] Polyolefins, including polyethylene, are increasingly consumed in many applications, including packaging for food and other goods, automotive components, fibers, and various manufactured articles. However, the large-scale use of polyolefins has raised concerns about the environmental impact of waste generated after first use.

[0003] In fact, currently a large amount of waste plastic materials comes from the differentiated recycling of urban plastic waste, also known as post-consumer waste (PCW), mainly consisting of flexible packaging (cast film, blown film and bi-directional oriented film), rigid packaging, blow-molded and injection-molded containers. Usually, through a separation step from other polymers such as PVC, PET or PS, two main polyolefin fractions are obtained, namely ethylene polymers (especially HDPE, LDPE, LLDPE) and propylene polymers (homopolymers, random copolymers, heterophasic copolymers).

[0004] However, the multi-component nature of recycled materials often results in low mechanical properties.

[0005] In order to mitigate the degradation of such mechanical properties, the art has proposed a solution of blending with nascent polymers. For example, according to WO2021064127, the impact strength of polyethylene mainly from waste streams is improved by blending polyethylene mainly from waste streams with nascent HDPE having a MIP (melt index at 190°C and 5kg load, ISO 1133) of 0.001 g / 10min to 0.50 g / 10min.

[0006] The examples report polymer blends where nascent HDPE is prepared by sequential polymerization in a cascade reactor.

[0007] However, scrap recycled polyethylene, in addition to poor impact strength, generally lacks adequate environmental stress crack resistance (ESCR) and cannot be easily processed into final products with satisfactory properties using conventional techniques.

[0008] In particular, the presence of propylene polymer as a contaminant can reduce the weld strength of welds in blow-molded articles.

[0009] Furthermore, it is difficult to obtain the optimum expansion ratio values ​​required for obtaining articles with controlled, uniform wall thickness in the blow molding process using scrap recycled polyethylene.

[0010] It has now surprisingly been found that blow moulded articles having valuable mechanical properties, in particular ESCR and weld strength, can be readily obtained from a polyethylene composition comprising scrap recycled polyethylene and at least trimodal polyethylene having appropriately selected characteristics using conventional blow moulding techniques and conditions. Summary of the invention

[0011] Accordingly, the present disclosure provides a polyethylene composition comprising:

[0012] I) 25 to 85 wt%, preferably 40 to 60 wt% of waste recycled polyethylene;

[0013] II) 15 to 75 wt. %, preferably 40 to 60 wt. % of a polyethylene having at least trimodal molecular weight distribution, the polyethylene having at least trimodal molecular weight distribution having:

[0014] 1) From 0.950g / cm 3 Up to 0.960g / cm 3 , preferably from 0.950 g / cm 3 Up to 0.958g / cm 3 Density, measured at 23°C according to ISO 1183-1:2012;

[0015] 2) MIF from 6 g / 10 min to 12 g / 10 min, preferably from 8 g / 10 min to 12 g / 10 min, wherein MIF is the melt flow index at 190° C. and 21.60 kg load, measured according to ISO 1133-1 2012-03;

[0016] 3) MIP from 0.20 g / 10 min to 1.0 g / 10 min, preferably from 0.30 g / 10 min to 0.80 g / 10 min, more preferably from 0.35 g / 10 min to 0.80 g / 10 min, wherein MIP is the melt flow index at 190°C and 5 kg load, determined according to ISO 1133-1 2012-03; and

[0017] 4) a MIF / MIP ratio of from 12 to 30, preferably from 15 to 30, more preferably from 15 to 25;

[0018] The weight contents of component I) and component II) are relative to the total weight of the sum of I) and II).

[0019] Even when the waste recycled polyethylene (I) contains a relatively high content of polypropylene, the present composition provides a final article having valuable mechanical properties. DETAILED DESCRIPTION

[0020] Preferably, the polyethylene composition has a molecular weight from 0.945 g / cm 3 Up to 0.962g / cm 3 , more preferably from 0.950 g / cm 3 Up to 0.960g / cm 3 density.

[0021] The MIF of the present polyethylene composition is preferably 5 g / 10 min to 30 g / 10 min, more preferably 10 g / 10 min to 25 g / 10 min.

[0022] The MIP of the present polyethylene composition is preferably 0.3 g / 10 min to 5 g / 10 min, more preferably 0.5 g / 10 min to 3 g / 10 min, most preferably 0.5 g / 10 min to 1 g / 10 min.

[0023] The MIE of the present polyethylene composition is preferably from 0.05 g / 10 min to 5 g / 10 min, more preferably from 0.1 g / 10 min to 1 g / 10 min, most preferably from 0.1 g / 10 min to 0.5 g / 10 min.

[0024] As mentioned above, the waste recycled polyethylene (I) is polyethylene recovered from plastic waste.

[0025] The recycling process typically includes standard waste handling, including collection, shredding, sorting and washing.

[0026] Therefore, the waste recycled polyethylene (I) generally contains a small amount of other polymers and / or inorganic components. Specifically, the waste recycled polyethylene (I) according to the present disclosure may contain a propylene polymer content of 1 wt % to 15 wt %, preferably 3 wt % to 10 wt %, based on the total weight of the waste recycled polyethylene.

[0027] The waste recycled polyethylene (I) is preferably PCW, i.e. post-consumer waste, but it may also contain pre-consumer waste (Pre-CW). The PCW is waste from at least one use cycle. The Pre-CW is plastic waste diverted from the manufacturing process that has not been reused, such as reprocessed, regrinded or scrapped, and has not been reincorporated into the same process that generated it.

[0028] Thus, generally speaking, the waste recycled polyethylene (I) is material from the article manufacturing process.

[0029] Preferably, the waste recycled polyethylene (I) is high density polyethylene (HDPE).

[0030] It has a range from 0.940 g / cm 3 Up to 0.965g / cm3 density.

[0031] The MIF of the waste recycled polyethylene (I) is preferably 1 g / 10 min to 100 g / 10 min, more preferably 5 g / 10 min to 60 g / 10 min.

[0032] The MIP of the waste recycled polyethylene (I) is preferably 0.5 to 10 g / 10 min, more preferably 1 to 5 g / 10 min.

[0033] The MIE of the waste recycled polyethylene (I) is preferably 0.1 to 10 g / 10 min, more preferably 0.2 to 5 g / 10 min, wherein MIE is a melt flow index at 190° C. and 2.16 kg load, measured according to ISO 1133-12012-03.

[0034] The expansion ratio of the waste recycled polyethylene (I) is preferably 130% to 190%.

[0035] The stress crack resistance (measured by FNCT 6MPa / 50°C) of the waste recycled polyethylene (I) is preferably equal to or higher than 2h, in particular from 2h to 15h.

[0036] The waste recycled polyethylene (I) is commercially available.

[0037] Examples are represented by the grades sold under the trade name CirculenRecover HD5603 Silver or Ivory by LyondellBasell Industries.

[0038] The polyethylene component (II) is preferably a spun polyethylene.

[0039] The expression "virgin polyethylene" means that it is a polymer which has not yet undergone any processing to produce finished products (such as packaging films, pipes, bottles, containers) or semi-finished products (such as fibers or sheets for thermoforming).

[0040] Therefore, the nascent polyethylene undergoes no post-production processing, apart from possible pelletization, which is still considered part of the polymer production process.

[0041] Furthermore, the polyethylene component (II) preferably has at least one of the following additional features:

[0042] - MIE of 0.01 g / 10 min to 1 g / 10 min, more preferably from 0.05 g / 10 min to 0.5 g / 10 min;

[0043] - a stress cracking resistance equal to or higher than 50 h, in particular from 50 h to 200 h, measured by FNCT 6 MPa / 50 ° C;

[0044] - Expansion ratio from 130% to 180%;

[0045] -5kJ / m2 to 20kJ / m2 at -30°C 2 Charpy aCN fracture toughness.

[0046] The expression "at least trimodal molecular weight distribution" means that the polyethylene component (II) comprises at least three fractions with different molecular weights, in particular a first (A) low molecular weight fraction, a second (B) high molecular weight fraction and a third (C) ultra-high molecular weight fraction.

[0047] The molecular weight distribution curve of the resulting final polymer obtained by GPC (gas permeation chromatography) analysis can be regarded as a superposition of the molecular weight distribution curves of the polymer fractions and will therefore show three or more distinct maxima, or will at least be significantly broadened compared to the individual curves of the individual fractions.

[0048] Preferably, the polyethylene component (II) comprises 40 to 50 wt% of a low molecular weight ethylene homopolymer A), 25 to 40 wt% of a high molecular weight ethylene copolymer B) and 15 to 28 wt% of an ultrahigh molecular weight ethylene copolymer C).

[0049] All stated weight contents are relative to the total weight of A)+B)+C).

[0050] Preferably, the ethylene homopolymer A) has a MIE of from 30 g / 10 min to 120 g / 10 min, more preferably from 40 g / 10 min to 100 g / 10 min. 1.2 , where MIE 1.2 It is the melt flow index at 190°C and 1.2 kg load, measured according to ISO 1133-1 2012-03.

[0051] The density of the ethylene homopolymer A) is preferably equal to or higher than 0.962 g / cm 3 , more preferably equal to or higher than 0.965 g / cm 3 .

[0052] The ethylene copolymer B) has a MIP of preferably from 2 to 15 g / 10 min, more preferably from 3 to 10 g / 10 min.

[0053] The density of the ethylene copolymer B) is preferably equal to or higher than 0.955 g / cm 3, especially from 0.955 g / cm 3 Up to 0.960g / cm 3 .

[0054] The ethylene copolymer C) has a MIF of preferably from 0.1 to 5 g / 10 min, more preferably from 0.2 to 2 g / 10 min.

[0055] The density of the ethylene copolymer C) is preferably equal to or higher than 0.950 g / cm 3 , especially from 0.950 g / cm 3 Up to 0.954g / cm 3 .

[0056] The comonomer or comonomers present in these ethylene copolymers are generally chosen from olefins having the formula CH2=CHR, wherein R is a linear or branched alkyl radical having from 1 to 10 carbon atoms.

[0057] Specific examples are propylene, butene-1, pentene-1, 4-methylpentene-1, hexene-1, octene-1 and decene-1. Particularly preferred comonomers are butene-1 and hexene-1.

[0058] Preferably, the ethylene copolymer B) contains 0.2 to 0.5 wt.-% of comonomer, based on the total weight of the copolymer.

[0059] Preferably, the ethylene copolymer C) contains from 1 to 2 wt. % of comonomer, based on the total weight of the copolymer.

[0060] It has been found that the polyethylene component (II) can be prepared by using a Ziegler-Natta catalyst in the polymerisation.

[0061] Ziegler-Natta catalysts include the reaction product of an organometallic compound of Group 1, 2 or 13 of the Periodic Table of Elements and a transition metal compound of Group 4 to 10 of the Periodic Table of Elements (using the new numbering system). In particular, the transition metal compound may be selected from compounds of Ti, V, Zr, Cr and Hf, and is preferably supported on MgCl2.

[0062] Particularly preferred catalysts comprise the reaction product of said organometallic compound of Group 1, 2 or 13 of the Periodic Table of Elements and a solid catalyst component comprising a Ti compound supported on MgCl2.

[0063] Preferred organometallic compounds are organo-Al compounds.

[0064] Thus, in a preferred embodiment, the polyethylene component (II) is obtainable by using a Ziegler-Natta polymerization catalyst, more preferably a Ziegler-Natta catalyst supported on MgCl, even more preferably a Ziegler-Natta catalyst comprising the reaction product of:

[0065] a) a solid catalyst component comprising a Ti compound supported on MgCl2 and optionally an electron donor compound ED (internal electron donor);

[0066] b) an organo-Al compound; and optionally

[0067] c) External electron donor compounds ED ext .

[0068] Preferably, in component a), when ED is present, the ED / Ti molar ratio ranges from 1.5 to 3.5, and the Mg / Ti molar ratio is higher than 5.5, in particular from 6 to 80.

[0069] Suitable titanium compounds are tetrahalides or compounds of the formula TiX n (OR 1 ) 4-n A compound wherein 0≤n≤3, X is halogen, preferably chlorine, and R 1 C1 to C 10 Hydrocarbyl group.

[0070] Titanium tetrachloride is the preferred compound.

[0071] The optional ED compound is generally selected from alcohols, ketones, amines, amides, nitriles, alkoxysilanes, aliphatic ethers and esters of aliphatic carboxylic acids.

[0072] Excellent results have been achieved using ester compounds, so ester compounds are particularly preferred as electron donors. Specific examples of esters are C1 to C20 aliphatic carboxylic acid alkyl esters, and particularly C1 to C8 aliphatic monocarboxylic acid alkyl esters, such as ethyl acetate, methyl formate, ethyl formate, methyl acetate, propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate. In addition, aliphatic ethers, and particularly C2 to C20 aliphatic ethers, such as tetrahydrofuran (THF) or dioxane, are also preferred.

[0073] Optionally, an external electron donor compound ED used to prepare the Ziegler-Natta catalyst ext The ED used in the solid catalyst component a) may be equal to or different from that used. It is preferably selected from the group consisting of ethers, esters, amines, ketones, nitriles, silanes and mixtures thereof. In particular, it may advantageously be selected from C2 to C20 aliphatic ethers, and in particular preferably cyclic ethers having 3 to 5 carbon atoms, such as tetrahydrofuran and dioxane.

[0074] The polymerization can be continuous or batchwise, according to known techniques and carried out in the liquid phase, in the presence or absence of an inert diluent, or in the gas phase or by liquid-gas mixing techniques.

[0075] In particular, for the preparation of the ethylene polymer fractions A), B) and C), the polymerization process can be carried out in three or more reactors connected in series, wherein the fractions are prepared in separate subsequent stages, in each stage except the first one, operating in the presence of the polymer formed and of the catalyst used in the previous stage.

[0076] The catalyst may be added to the first reactor only, or to more than one reactor.

[0077] Reaction time, pressure and temperature are not critical with respect to the polymerization step, however it is optimal if the temperature is between 50° C. and 100° C. The pressure may be atmospheric pressure or higher, in particular in the range of 0.15 MPa to 1 MPa.

[0078] The molecular weight is adjusted by using known regulators, in particular hydrogen.

[0079] For more details, see WO2004058876.

[0080] Alternatively, although less practical, the ethylene polymer fractions A), B) and C) may be prepared separately, operated in a single reactor under the conditions described above, and then the fractions may be mechanically blended together.

[0081] The polyethylene composition may contain conventional additives. Examples of these additives are heat stabilizers, antioxidants, UV absorbers, light stabilizers, metal deactivators, peroxide-destroying compounds and alkaline co-stabilizers, preferably in an amount of 0.05 to 10% by weight, more preferably 0.05 to 5% by weight, based on the total weight of the polyethylene composition.

[0082] The polyethylene composition may further comprise fillers, reinforcing agents, plasticizers, lubricants, emulsifiers, pigments, fluorescent whitening agents, flame retardants, antistatic agents, foaming agents or combinations thereof, preferably in a total content of 1 to 50 weight % of the total weight of the polyethylene composition.

[0083] The present polyethylene composition can be obtained by melting and mixing the components, and the mixing is carried out in a mixing device at a temperature of generally 160°C to 250°C.

[0084] Any known devices and techniques may be used for this purpose.

[0085] Melt mixing apparatuses useful in this context are in particular extruders or kneaders, particularly preferably twin-screw extruders. It is also possible to premix the components at room temperature in a mixing apparatus.

[0086] As mentioned previously, the present polyethylene composition can be advantageously used for the production of blow-molded articles.

[0087] In particular, the polyethylene composition has particularly good suitability for producing small blow-molded articles.

[0088] Preferred examples of the small-sized blow-molded articles are blow-molded articles having a capacity of 250 ml to 5000 ml, such as small containers, cans, and bottles.

[0089] In fact, preferably, it is characterized by an environmental stress cracking resistance (measured by FNCT 6MPa / 50°C) equal to or higher than 15h, more preferably equal to or higher than 18h, in particular from 15h to 50h or from 18h to 50h.

[0090] The expansion ratio of the present polyethylene composition is preferably from 130% to 180%.

[0091] The Charpy aCN fracture toughness of the polyethylene composition at -30°C is preferably from 3 kJ / m2 to 10 kJ / m 2 .

[0092] Details of the test methods are given in the examples.

[0093] The blow molding process is generally performed as follows: the polyethylene composition is first plasticized at a temperature of 180° C. to 250° C. in an extruder, and then extruded through a die into a blow molding die for cooling.

[0094] Example

[0095] The practice and advantages of various embodiments, compositions and methods as provided herein are disclosed in the following examples below. These examples are merely illustrative and are not intended to limit the scope of the appended claims in any way.

[0096] The following analytical methods were used to characterize the polymer compositions.

[0097] Melt flow index

[0098] The measurement was carried out at 190°C with a specified load according to ISO 1133-1 2012-03.

[0099] density

[0100] Measured at 23°C according to ISO 1183-1:2012.

[0101] Expansion ratio

[0102] Using a capillary rheometer The expansion ratio of the investigated polymers was measured at T = 190°C using a Rheotester 2000 and a Rheograph 25 capillary rheometer equipped with a commercial 30 / 2 / 2 / 20 die (total length 30 mm, effective length = 2 mm, diameter = 2 mm, L / D = 2 / 2 and 20° inlet angle) and an optical device for measuring the thickness of the extruded strand (from The sample was melted in a capillary tube at 190°C for 6 min and heated to a temperature corresponding to 1440 s -1 The piston speed at the die is the shear rate obtained by extrusion.

[0103] When the piston reaches a position of 96 mm from the die inlet, the extrudate is cut at a distance of 150 mm from the die outlet (by The laser diode was used to measure the extrudate diameter as a function of time at a distance of 78 mm from the die exit. The maximum value corresponds to D 挤出物 The expansion ratio is determined by the following calculation:

[0104] SR=(D 挤出物 -D 压模 )100% / D 压模

[0105] Where D 压模 is the corresponding diameter at the die exit measured with a laser diode.

[0106] Environmental stress cracking resistance according to the full notch creep test (FNCT)

[0107] The environmental stress cracking resistance of the polymer samples was determined in aqueous surfactant solution according to the international standard ISO 16770 (FNCT). 10 mm thick molded sheets were prepared from the polymer samples. Rods with a square cross section (10 mm×10 mm×100 mm) were notched on four sides perpendicular to the stress direction using a razor blade. A sharp notch with a depth of 1.6 mm was made using the notching device described by M. Fleissner in Kunststoffe 77 (1987), page 45.

[0108] Calculate the applied load from the tensile force divided by the initial ligament area. Ligament area is the residual area = total cross-sectional area of ​​the specimen minus the cut area. For FNCT specimens: 10 mm 2 ×10mm 2 -4 times the trapezoidal cut area = 46.24mm 2(Failure process / remaining cross section for crack extension). The test specimens were loaded with a constant load of 6 MPa at 50°C using the standard conditions recommended by ISO 16770 in a 2% (by weight) aqueous solution of the nonionic surfactant ARKOPAL N100. The time at which the test specimens broke was detected.

[0109] Charpy aCN

[0110] The fracture toughness is determined by an in-house method on test bars with dimensions of 10 mm × 10 mm × 80 mm, which have been sawn from a molded sheet with a thickness of 10 mm. Six of these test bars are notched in the center using a razor blade from the notching device described above for FNCT. The notch depth is 1.6 mm. The measurement is carried out essentially in accordance with the Charpy measurement method according to ISO 179-1, but with modifications to the test specimens and the impact geometry (support spacing). All test specimens are conditioned to a measuring temperature of -30°C over a period of 2 to 3 hours. The test specimens are then placed without delay on the supports of the pendulum impact tester according to ISO 179-1. The distance between the supports is 60 mm. The fall of a 2J hammer is triggered, with the fall angle set to 160°, the pendulum length being 225 mm and the impact velocity being 2.93 m / s. The fracture toughness values ​​are expressed in kJ / m 2 is indicated and is given by the quotient of the impact energy consumed and the initial cross-sectional area aCN at the notch. Only the values ​​for complete fracture and hinge fracture can be used here as a basis for a common meaning (see the recommendations of ISO 179-1).

[0111] Welding quality

[0112] 22 g blow-molded bottles having an inner volume of 310 ml and an average wall thickness of 0.8 mm were produced using a W. Müller molding machine (model Blowtec BFB 1 / 4).

[0113] The machine parameters are:

[0114] -Processing temperature: 200℃;

[0115] -Mold temperature: 12°C;

[0116] - Molding cycle time: 15 seconds;

[0117] - Blow molding pressure: 5 bar;

[0118] -Production capacity: 7Kg / h.

[0119] After deburring, a bottom weld sample was cut from each of the bottles thus obtained. Then, these bottom weld samples were manually bent twice and manually torn. If the sample did not break along the weld, it was classified as "good", and if it broke, it was classified as "bad".

[0120] Comonomer content

[0121] The comonomer content was determined by IR using a FT-IR spectrometer Tensor 27 from Bruker calibrated with a stoichiometric model for the determination of ethyl side chains in PE (butene-1 as comonomer) according to ASTM D 6248 98. The results were compared with the estimated comonomer content obtained from the mass balance of the polymerization process and were found to be consistent.

[0122] Polypropylene content

[0123] 13 C NMR spectra were obtained on a Bruker Av-600 spectrometer equipped with a cryogenic probe, operating at 160.91 MHz in Fourier transform mode at 120 °C.

[0124] The peak of CH2 ethylene was used as an internal standard at 29.9 ppm. The sample was dissolved in 1,1,2,2-tetrachloroethane-d2 at 8 wt / v% concentration at 120 °C. A 90° pulse was used with a delay of 15 seconds between the pulse and CPD to remove 1 H- 13 Each spectrum was acquired with C coupling. 512 transients were stored in 32K data points using a spectral window of 9000 Hz.

[0125] The molar composition was obtained using the peak areas as follows (Table 1):

[0126] P=100A3 / S

[0127] E=0.5100A2 / S

[0128] Where S = 0.5A2 + A3

[0129] Monomer molecular weights were used to convert molar contents by weight.

[0130] Table 1: Distribution of PP / PE blends

[0131] serial number Chemical shift (ppm) carbon sequence 1 48.8-45.4 <![CDATA[CH2]]> P 2 29.9 <![CDATA[CH2]]> E 3 29.0-28.0 CH P 4 21.8-19.8 CH3 P

[0132] Example 1 and Comparative Example 1

[0133] Commercial grade sold by LyodellBasell Industries HD5603 Grey is used as waste recycled polyethylene (I).

[0134] HD5603 Grey is a PCW HDPE containing about 9 wt% (based on total weight) of propylene polymer and having the properties reported in Table 1 where it is identified as QCP 5603.

[0135] The polyethylene composition of Example 1 is prepared by mixing 50 wt % of QCP 5603 Grey was obtained by blending with 50 wt% PE-1, a polyethylene with trimodal molecular weight distribution, having the properties reported in Table 1.

[0136] The polyethylene PE-1 represents the component (II) of the present invention, and the polyethylene PE-1 is made of the following components: 45% by weight of a low molecular weight ethylene homopolymer A), the MI of the ethylene homopolymer A) 1.2 The density is about 75 g / 10 min and the density is about 0.968 g / cm 3 ; 33% by weight of a high molecular weight ethylene / butene-1 copolymer B), the ethylene / butene-1 copolymer B) having a MIP of 7.5 g / 10 min and a density of 0.958 cm 3 and 22 wt% of an ultra-high molecular weight ethylene / butene-1 copolymer C), the ethylene / butene-1 copolymer C) having a MIF of 0.65 g / 10 min and a density of 0.953 g / cm 3 .

[0137] The weight content is relative to the total weight of A)+B)+C).

[0138] The polyethylene PE-1 was prepared by a method similar to Example 1 of WO2004058876.

[0139] The polyethylene composition of Comparative Example 1 was prepared by mixing 50 wt % of QCP 5603Grey with 50 wt% ACP 5831D was blended for comparative purposes and has the properties reported in Table 1, where it is identified as 5831D.

[0140] ACP 5831D is a commercial polyethylene with trimodal molecular weight distribution sold by LyodellBasell Industries.

[0141] The exemplified polyethylene composition was prepared by blending the components in a twin screw extruder Leistritz ZSE27MAXX 44D operating at 250 rpm and at temperatures of 230° C. (first barrel) and 250° C. (second to tenth barrel and die).

[0142] The properties of the final composition thus obtained are reported in Table 2.

[0143] Table 1

[0144] QCP 5603 PE-1 5831D MIF[g / 10min] 45 9.9 20 MIP[g / 10min] 2.05 0.45 0.94 MIE[g / 10min] 0.4 0.1 0.21 <![CDATA[Density (g / cm 3 )]]> 0.958 0.954 0.958 Expansion ratio [%] 168 145 143 FNCT(50℃,6MPa)[h] 7 100 18 <![CDATA[ACN(-30℃)[kJ / m 2 ]]]> 2.5 8.0 7 Welding quality bad good good

[0145] Table 2

[0146] Example 1 Comparative Example 1 MIF[g / 10min] 18.7 28.7 MIP[g / 10min] 0.86 1.48 MIE[g / 10min] 0.2 0.3 <![CDATA[Density (g / cm 3 )]]> 0.956 0.958 Expansion ratio [%] 148 157 FNCT(50℃,6MPa)[h] 27 10 <![CDATA[ACN(-30℃)[kJ / m 2 ]]]> 4.3 4.1 Welding quality good bad

Claims

1. A polyethylene composition, comprising: I) 25 to 85 wt%, preferably 40 to 60 wt% of waste recycled polyethylene; II) 15 to 75 wt. %, preferably 40 to 60 wt. % of a polyethylene having at least trimodal molecular weight distribution, the polyethylene having at least trimodal molecular weight distribution having: 1) From 0.950g / cm 3 Up to 0.960g / cm 3 , preferably from 0.950 g / cm 3 Up to 0.958g / cm 3 Density, measured at 23°C according to ISO1183-1:2012; 2) MIF from 6 g / 10 min to 12 g / 10 min, preferably from 8 g / 10 min to 12 g / 10 min, wherein MIF is the melt flow index at 190° C. and 21.60 kg load, measured according to ISO 1133-1 2012-03; 3) MIP from 0.20 g / 10 min to 1.0 g / 10 min, preferably from 0.30 g / 10 min to 0.80 g / 10 min, more preferably from 0.35 g / 10 min to 0.80 g / 10 min, wherein MIP is the melt flow index at 190°C and 5 kg load, determined according to ISO 1133-1 2012-03; and 4) a MIF / MIP ratio of from 12 to 30, preferably from 15 to 30, more preferably from 15 to 25; The weight contents of component I) and component II) are relative to the total weight of the sum of I) and II).

2. The polyethylene composition according to claim 1, wherein the waste recycled polyethylene (I) is PCW.

3. The polyethylene composition according to claim 1 or 2, wherein the waste recycled polyethylene (I) has a molecular weight of from 0.940 g / cm 3 Up to 0.965g / cm 3 density.

4. The polyethylene composition according to claim 1 or 2, wherein the waste recycled polyethylene (I) has an expansion ratio of from 130% to 190%.

5. The polyethylene composition according to claim 1 or 2, wherein the polyethylene component (II) is a primary polyethylene.

6. The polyethylene composition according to claim 1 or 2, wherein the polyethylene component (II) is obtained by using a Ziegler-Natta polymerization catalyst.

7. The polyethylene composition according to claim 1 or 2, wherein the polyethylene component (II) comprises 40 to 50 wt% of a low molecular weight ethylene homopolymer A), 25 to 40 wt% of a high molecular weight ethylene copolymer B) and 15 to 28 wt% of an ultra-high molecular weight ethylene copolymer C).

8. The polyethylene composition according to claim 7, wherein the ethylene homopolymer A) has a MIE of from 30 g / 10 min to 120 g / 10 min, preferably from 40 g / 10 min to 100 g / 10 min. 1.2 , where MIE 1.2 is the melt flow index at 190°C and 1.2 kg load, measured according to ISO 1133-1 2012-03; the ethylene copolymer B) has a MIP from 2 g / 10 min to 15 g / 10 min, preferably from 3 g / 10 min to 10 g / 10 min; the ethylene copolymer C) has a MIF from 0.1 g / 10 min to 5 g / 10 min, preferably from 0.2 g / 10 min to 2 g / 10 min.

9. The polyethylene composition according to claim 7, wherein the ethylene homopolymer A) has a molecular weight equal to or higher than 0.962 g / cm 3 , preferably equal to or higher than 0.965 g / cm 3 The density of the ethylene copolymer B) is equal to or higher than 0.955g / cm 3 , especially from 0.955g / cm 3 Up to 0.960g / cm 3 and the ethylene copolymer C) has a density equal to or higher than 0.950g / cm 3 , especially from 0.950g / cm 3 Up to 0.954g / cm 3 density.

10. The polyethylene composition according to claim 1 or 2, wherein the polyethylene component (II) has at least one characteristic of at least one of the following additional characteristics: - MIE of 0.01 g / 10 min to 1 g / 10 min, preferably from 0.05 g / 10 min to 0.5 g / 10 min; - a stress cracking resistance equal to or higher than 50 h, in particular from 50 h to 200 h, measured by FNCT 6 MPa / 50 ° C; - Expansion ratio from 130% to 180%; -5kJ / m2 to 20kJ / m2 at -30°C 2 Charpy aCN fracture toughness.

11. The polyethylene composition according to claim 1 or 2, wherein the polyethylene composition has a molecular weight of from 0.945 g / cm 3 Up to 0.962g / cm 3 , more preferably from 0.950 g / cm 3 Up to 0.960g / cm 3 density.

12. The polyethylene composition according to claim 1 or 2, having an environmental stress crack resistance equal to or higher than 15h, more preferably equal to or higher than 18h, in particular from 15h to 50h or from 18h to 50h, measured by FNCT 6MPa / 50°C.

13. The polyethylene composition according to claim 1 or 2, having an expansion ratio of from 130% to 180%.

14. An article of manufacture comprising the polyethylene composition of claim 1.

15. The manufactured article according to claim 14, which is in the form of a blow-molded article, in particular a small blow-molded article having a capacity of 250ml to 5000ml.

Citation Information

Patent Citations

  • Polyethylene blow moulding composition for producing jerry cans

    WO2004058876A1

  • Mixed-plastic polyethylene blend

    WO2021064127A1